Strategi Pengembangan Program Sekolah Adiwiyata Nasional di Tingkat SMA Kota Pekanbaru - Nurhafni Nurhafni; Almasdi Syahza; Auzar Auzar; Nofrizal Nofrizal (Dinamika Lingkungan Indonesia, 2019)
School is an important vehicle for educating and fostering people to understand and understand a science. In realizing a caring and cultured school, the school community needs to be involved in various environmental learning activities. In addition, schools are also expected to involve the surrounding community in conducting various activities that benefit both the school community, the community and the environment. These activities include creating extracurricular / curricular activities in the field of participatory-based environment in schools, participating in environmental action activities carried out by outsiders, building partnership activities or initiating the development of environmental education in schools, management and development of school supporting facilities. . School is a community that consists of students, teachers, principals, and administration and employees which is one of the effective mediums for learning and awareness of school residents. So that individuals, ranging from teachers, students and workers are involved in efforts to stop the rate of environmental damage caused by human hands. Creating a caring and cultured school requires a school management strategy that supports the implementation of environmental education by all school members in accordance with the basic principles of the Adiwiyata Program which is participatory and sustainable.